Cioccolato Jar / Imran Abdul Hamid @ Hamid - Abdul Hamid @ Hamid, Imran (2021)
Cioccolato Jar is a business that are selling Choco jar of multiple types as their main product. The types of Choco jar that Cioccolato Jar sell are original Cioccolato jar which use melted milk chocolate as their base and Cioccolato White which use melted white chocholate. Both types come with 2 choice of cereal which is bubble rice and baby crunch. Cioccolato Jar Products are suitable for everyone regardless of their age and gender as it does not contain any harmful ingredients. For now, Our Target market are teenagers and kids as they tend to like sweet snacks. Cioccolato Jar currently operates in Klang and through online only. This due to Cioccolato Jar is fully operates from the home of the founder. Cioccolato Jar is promoting their products on Facebook. Currently our Facebook page has reached 133 total likes. We are expecting the number to grow in the future. Cioccolato Jar is owned and managed by Imran Bin Abdul Hamid @ Hamid, a student of UiTM Selangor. He is the sole founder of Cioccolato and he alone produce all the products by himself. Imran manages the business from home and provide delivery across all states in Malaysia including Sabah and Sarawak by using the courier service such as J&t Express and Dhl eCommerce. In the future, we expect this business to grow successfully as the demand of the chocojar are high and chocolate is the most favored snacks for all layer of generations.